1992
DOI: 10.1073/pnas.89.1.402
|View full text |Cite
|
Sign up to set email alerts
|

Interferons and interleukin 6 suppress phosphorylation of the retinoblastoma protein in growth-sensitive hematopoietic cells.

Abstract: One approach to identify postreceptor molecular events that transduce the negative-growth signals of inhibitory cytokines is to analyze the cytokine-induced modifications in the expression of cell-cycle-controlling genes. Here we report that suppression of phosphorylation of the retinoblastoma gene product (pRb) is a receptor-generated event triggered by interferons and interleukin 6 (IL-6) in hematopoietic cell lines. The conversion of pRb to the underphosphorylated forms occurs concomitantly with the decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 43 publications
9
101
0
Order By: Relevance
“…Consistent with this ®nding, an increased level of p21 WAF1/CIP1 along with accumulation of hypophosphorylated pRb protein, have been detected in M1 leukemia cells induced to di erentiate by IL-6 treatment (Resnitzky et al, 1992). Furthermore, treatment of B16 ± F10.9 mouse metastatic melanoma cells with IL-6 in the presence of exogenously added soluble IL-6R alpha subunit (gp 80) was shown recently to induce growth arrest, differentiation and expression of p21 WAF1/CIP1 (Oh et al, 1997).…”
Section: Introductionsupporting
confidence: 77%
“…Consistent with this ®nding, an increased level of p21 WAF1/CIP1 along with accumulation of hypophosphorylated pRb protein, have been detected in M1 leukemia cells induced to di erentiate by IL-6 treatment (Resnitzky et al, 1992). Furthermore, treatment of B16 ± F10.9 mouse metastatic melanoma cells with IL-6 in the presence of exogenously added soluble IL-6R alpha subunit (gp 80) was shown recently to induce growth arrest, differentiation and expression of p21 WAF1/CIP1 (Oh et al, 1997).…”
Section: Introductionsupporting
confidence: 77%
“…To understand the mechanism of IFN-mediated growth-inhibition of cells in the G0/G1-phase of the cell-cycle, we and others have earlier shown that IFNa-treatment of Daudi cells leads to enhanced expression of under-phosphorylated form of pRB (Kumar and Atlas, 1992;Resnitzky et al, 1992). To illustrate this e ect, Figure 1 shows the kinetics of inhibition of pRB phosphorylation ( Figure 1a) and inhibition of CDK-2 associated H-1 kinase activity without any e ect on CDK-2 expression (Figure 1b).…”
Section: Ifn-a Inhibits Rb Protein Phosphorylation and Cdkassociated mentioning
confidence: 99%
“…To understand the mechanism of inhibitory e ect of IFN in the G0/G1-phase of the cell cycle, we and others have earlier shown that IFN-a enhances the expression of underphosphorylated RB protein (pRB) by inhibiting the pRB phosphorylation in human Burkitt's lymphoma Daudi cells (Burke et al, 1992;Kumar and Atlas, 1992;Resnitzky et al, 1992). We have also demonstrated that IFN-g inhibits the growth of human epidermoid A-431 cells in the G0/G1-phase of the cell cycle (Kumar and Mendelsohn, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanisms of growth suppression, IFNs have been reported to induce down-regulation of c-myc (Einat et al, 1985), dephosphorylation of the retinoblastoma susceptibility gene product (pRB) (Resnitzky et al, 1992), inhibition of both cyclins and cyclin-dependent kinases (CDK) in their expression and activities (Thomas, 1988;Yamada et al, 1994), induction of CDK inhibitors (Chin et al, 1996;Sangfelt et al, 1997) and modulation of E2F activity (Melamed et al, 1993). IFNs can also suppress the signaling pathway of growth factors such as plateletderived growth factor and interleukin-6, which may contribute to growth inhibition of factor-dependent cells (Xu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%